The principle of legality and the legitimacy of the punitive power - Miró Quesada Gayoso, Josefina (2024)
The principle of legality needs to transcend its formal dimension to address the arbitrariness of punitive power and rationalize its interventions. In light of new social, economic, political, and legal contexts, an approach focused solely on the formal aspects of a criminal provision is insufficient to ensure that its design and application serve, not merely to coerce, but to communicate and reaffirm values and principles derived from the constitutional and international human rights legal order.In this article, the author describes the metamorphosis that the principle of legality has undergone since its Enlightenment origins to question the relevance of some of its traditional subguarantees. This situation requires imbuing the principle of legality with an axiological content that allows legal practitioners to reconcilie the legality with the legitimacy of the punitive power represented in a criminal provision.